If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(7 + x) = 0 (7 * -1 + x * -1) = 0 (-7 + -1x) = 0 Solving -7 + -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -1x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -1x = 0 + 7 -1x = 0 + 7 Combine like terms: 0 + 7 = 7 -1x = 7 Divide each side by '-1'. x = -7 Simplifying x = -7
| a=(5a-6) | | 3(x+2)+4(x-5)=10(x+4) | | -9=(-10) | | 4c-6whenc=3 | | a=(3a-7) | | 6(x+16)= | | (5x+2)(5x+2)=144 | | X-8=-4-26 | | 7x-3x-50=20 | | y-2(y-3)+4= | | 2x+3x-5=50 | | 35z-11=59 | | x=6(2x+1) | | -4-6=5x+9-4x | | 0(8b+4)= | | 26R-3R^2=0 | | 11x+3=2x | | -75=-3x+3 | | 4x-9-9-8x= | | 5j-j= | | X+X+10+2(2X+10)=180 | | 8h-4h= | | -9t+3=-10t | | 2x-(4y-3)+5+-3+-1= | | -(4xy-10)+3(3xy+6)= | | 6+4r=5r | | 3-3*6-2=12 | | 18-r=-323 | | -15x-14= | | 4x-1=10x+8 | | 22+z=-180 | | Y=x+-5 |